The Influence of the Usefulness of Electronic Word of Mouth Information on Tourists' Visiting Intentions - Arifah, Muhammad Syahroni; Mariam, Siti; Ramli, Abdul Haeba (Jurnal Ilmiah Manajemen Kesatuan, 2024)
This study aims to examine the effect of argument quality, source credibility, information needs, and quantity of Electronic Word of Mouth (EWOM) information on information usefulness and the effect of information usefulness on visiting intentions. This research focuses on Tiktok social media users who are looking for information about tourist attractions in the Thousand Islands. The method used in this research is quantitative method with Structural Equation Modeling (SEM) technique using SmartPLS 3.0 software. Data were collected through an online survey involving 120 respondents. The results showed that argument quality, source credibility, and EWOM information needs have a significant positive influence on the usefulness of EWOM information. However, information quantity does not have a significant influence on information usefulness. In addition, information usefulness is shown to have a significant positive influence on visit intention. This research provides important implications for digital marketing strategies, particularly in the context of tourism, by emphasizing the importance of the quality and relevance of information delivered through social media platforms such as Tiktok. The findings also show that although the quantity of information available is high, the quality of relevant and credible information remains a key determinant in increasing information usability and driving consumer intention to visit. This research is expected to contribute to the EWOM literature and become a reference for the development of marketing strategies in the digital era.Keywords: EWOM, information usefulness, visit intention, source credibility, argument quality